Expanding horizons for tourism at Rio da Prata/Campo Grande from the perspective of public use in the Pedra Branca State Park (RJ) - Oliveira, Maria Amália Silva Alves de; Pena, Ingrid Almeida de Barros; Peixoto, Roberta (Revista Turismo em Análise, 2020)
This work investigates the tourism process of Rio da Prata, an area inside Pedra Branca State Park, through the viewpoint of Public Use, considering that the knowledge produced from public use processes is relevant to the planning and management of visitation activities which aim at conservation. Literature review, semi-open questionnaires, interviews and participant observation were carried out. Residents, visitors, technicians from the environmental agency and local guides were consulted. Based on the information collected, we discuss the representations of tourism, the opportunities and challenges related to Public Use, and the results of the “PEPB Local Guide Training Course”. We present recommendations for future qualifications offered by the environmental agency and conclude that in addition to the environmental agency, other sectors should be involved in local tourism promotion.